The Degree to Which a Sample of Parents Practice Islamic Child-Rearing Methods in Modifying Stubborn Behavior in Their Children - Al-Refai, Nader; Mohaidat, Farah (Millah: Journal of Religious Studies, 2025)
This study aimed to reveal the extent to which a sample of parents were found to practice Islamic child-rearing methods to modify stubborn behavior in their children. In addition, it aims to demonstrate the extent to which there are statistically significant differences in the level of parents’ practice of Islamic child-rearing methods in modifying stubborn behavior in children based on the variables of social role, level of education, employment status, and the number of children. The study adopted the descriptive analytical approach using the field survey method as it was deemed well-fitted to the nature of the study and its objectives. To achieve the objectives of the study, a questionnaire was constructed to collect data from parents. The sample consisted of 317 fathers and mothers, who were selected via the convenience method during the first semester of the academic year 2021-2022. The study revealed a set of important results. Most prominently, the extent to which parents practice Islamic parenting methods in modifying stubborn behavior in children was high, with the method of encouragement being most commonly used, and the method of exclusion (isolation) being the least used. The results also indicated that there were no statistically significant differences at the significance level (α = 0.05) based on the variables of social role, educational level, and employment status. There are significant differences between the arithmetic averages due to the variable of the number of children. The study recommended encouraging institutions concerned with the family in Jordanian society to focus their attention on conducting training courses for mothers and fathers, to help them learn and practice behavior modification strategies as found in Islamic teachings and to provide them with appropriate support materials for doing so.